Legal Protection For Outsourcing Workers Based On Perpu No. 2 of 2022 Concerning Employment Creation - Simon Andrean Sudarso; Miftakhul Huda (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
Today, many companies use outsourcing workers to support their operations. Of course, these outsourced workers expect legal protection that guarantees their rights. At the end of 2022, the government issued Perpu No. 2 of 2022 concerning Job Creation. In this regard, this research examines the Legal Protection for Outsourcing Workers based on Perpu No. 2 of 2022 concerning Job Creation and the Legal Consequences of Outsourcing Companies That Do Not Meet Applicable Legal Provisions. This research concludes that the form of protection for outsourced workers is contained in Article 81 number 20 of Perpu Number 2 of 2022 concerning Job Creation. Outsourced workers also receive legal protection through the TUPE Principle (Transfer of Undertaking Protection of Employment) and there are legal consequences if the outsourcing company does not comply with applicable legal provisions. The outsourcing company may be subject to criminal and administrative sanctions.